A Fijivirus Major Viroplasm Protein Shows RNA-Stimulated ATPase Activity by Adopting Pentameric and Hexameric Assemblies of Dimers - Gabriela Llauger; Roberto Melero; Demián Monti; Gabriela Sycz; Cristián Huck-Iriart; María L. Cerutti; Sebastián Klinke; Evelyn Mikkelsen; Ariel Tijman; Rocío Arranz; Victoria Alfonso; Sofía M. Arellano; et al. (mBio, 2023)
ABSTRACT Fijiviruses replicate and package their genomes within viroplasms in a process involving RNA-RNA and RNA-protein interactions. Here, we demonstrate that the 24 C-terminal residues (C-arm) of the P9-1 major viroplasm protein of the mal de Río Cuarto virus (MRCV) are required for its multimerization and the formation of viroplasm-like structures. Using an integrative structural approach, the C-arm was found to be dispensable for P9-1 dimer assembly but essential for the formation of pentamers and hexamers of dimers (decamers and dodecamers), which favored RNA binding. Although both P9-1 and P9-1ΔC-arm catalyzed ATP with similar activities, an RNA-stimulated ATPase activity was only detected in the full-length protein, indicating a C-arm-mediated interaction between the ATP catalytic site and the allosteric RNA binding sites in the (do)decameric assemblies. A stronger preference to bind phosphate moieties in the decamer was predicted, suggesting that the allosteric modulation of ATPase activity by RNA is favored in this structural conformation. Our work reveals the structural versatility of a fijivirus major viroplasm protein and provides clues to its mechanism of action. IMPORTANCE The mal de Río Cuarto virus (MRCV) causes an important maize disease in Argentina. MRCV replicates in several species of Gramineae plants and planthopper vectors. The viral factories, also called viroplasms, have been studied in detail in animal reovirids. This work reveals that a major viroplasm protein of MRCV forms previously unidentified structural arrangements and provides evidence that it may simultaneously adopt two distinct quaternary assemblies. Furthermore, our work uncovers an allosteric communication between the ATP and RNA binding sites that is favored in the multimeric arrangements. Our results contribute to the understanding of plant reovirids viroplasm structure and function and pave the way for the design of antiviral strategies for disease control.